Interface defects within the junction region and its effect on the electrical and optical properties of a heterojunction solar cell - Mussab J. Ahmed; Ayed N. Saleh (Tikrit Journal of Pure Science)
The simulation model used in this study is the heterojunction solar cell with SnS absorption layer using the AFORS-HET simulation program. Where the effect of interface defect density (Nit) and the location of these levels within the interface on the electrical and optical properties was studied. Through the study, we learned the effect of the locations of the energy levels for defects within the junction, and it was found that the largest effect of the defects is within the locations of the deep energy levels, D.deep traps and A.deep traps within the junction. After that, the effect of interface defect density and its relationship to thickness and impurities concentration of both the buffer and absorption layer were studied, as the increase in the thickness of the absorption layer indicated a clear decrease in the effect of the density of the interface cases, otherwise the increase in the thickness of the buffer layer did not reduce the effect of these defects. The effect of the interface defect density increases with increasing the concentration of impurities in the SnS absorption layer, the effect of the density of the interlayer defects decreases with the increase in the concentration of impurities in the buffer layer.